2018
DOI: 10.1002/wps.20491
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of psychosis across protocols and risk cohorts using automated language analysis

Abstract: Language and speech are the primary source of data for psychiatrists to diagnose and treat mental disorders. In psychosis, the very structure of language can be disturbed, including semantic coherence (e.g., derailment and tangentiality) and syntactic complexity (e.g., concreteness). Subtle disturbances in language are evident in schizophrenia even prior to first psychosis onset, during prodromal stages. Using computer-based natural language processing analyses, we previously showed that, among English-speakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
264
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 302 publications
(277 citation statements)
references
References 38 publications
9
264
1
3
Order By: Relevance
“…For example, recent research (Çokal et al, 2019) showed that only syntactically motivated and not general pause patterns reliably distinguished participants with schizophrenia from non-clinical controls. Further, automated measures of semantic coherence are being developed to assess symptoms like tangentiality (Corcoran et al, 2018). It is an open question how they relate to vocal patterns and how they can complement each other.…”
Section: Overviewmentioning
confidence: 99%
“…For example, recent research (Çokal et al, 2019) showed that only syntactically motivated and not general pause patterns reliably distinguished participants with schizophrenia from non-clinical controls. Further, automated measures of semantic coherence are being developed to assess symptoms like tangentiality (Corcoran et al, 2018). It is an open question how they relate to vocal patterns and how they can complement each other.…”
Section: Overviewmentioning
confidence: 99%
“…Computational psychiatry, which focuses on the development of mechanistic models linking clinical symptoms to neurobiology and observed behavior through computational parameters, has already begun to describe the neurobiology of learning under volatile conditions (26), and to help mental health researchers improve prognostic prediction (27) and to make plans to more precisely target therapeutics (28). A computational psychiatry of social interaction holds promise for honing existing treatments and building new ones in BPD and other disorders with prominent interpersonal symptomatology (29).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the previously described studies in this area involve computing a notion of semantic coherence in language with the use of word embeddings in high-dimensional vector space, either with LSA or neural word embedding techniques [7,8,9,10]. In nearly all cases, word and sentence/phrase embedding pairs, denoted by vectors a and b, are evaluated with the notion of cosine similarity, a measure of the cosine of the angle θ a,b between the two vectors.…”
Section: Semantic Coherencementioning
confidence: 99%